Ethnobotanical survey of anti-diabetic plants in some local Government areas in Ogun State, Nigeria (2005)
The results of an ethnobotanical survey of plants used in the treatment of diabetes in Ipokia, Haro and Ijebu North Local Government Areas of Ogun State are reported. Thirty four plant species in twenty families and some twenty recipes were identified Anthocleista vogelii Planch, Anthocleista djalonensis A. Chev, Bridelia ferruginea Benth, Clobimethula braunii (Engl) van Tiegh, Momordica charantia Linn and Musa sapientum Linn were prominent in the recipes. These phytomedicine were administered as concoction, decoctions, and powder of ash residue. Previous biological studies of some of the plants confirm the rational use of the recipes by traditional healers. Field study of plants and their specific uses by traditional healers eliminate random collection and it is an important phase in the identification, screening and subsequent isolation of bioactive compounds from the plants. A systematic scientific research into the efficacy of these medicinal plants is suggested.